Physical activity and school adaptation among Chinese junior high school students: chain mediation of resilience and coping styles - Wu, Xinbo; Liang, Junwen; Chen, Jiaxi; Dong, Weixin; Lu, Chunxia (Frontiers in Psychology, 2024)
Background:As a crucial juncture in students' educational journey, junior high school presents challenges that profoundly influence well-being and academic performance. Physical activity emerges as a pivotal factor shaping the holistic development of junior high school students. Beyond its recognized impact on physical and mental health, engaging in regular physical activity proves effective in augmenting students' adaptability to school life. Despite its importance, the mechanisms through which physical activity influences school adaptation in junior high school students remain understudied in academic research. Objective: In exploring the potential mechanisms, this study aims to validate the mediating roles of resilience and coping styles by examining the association between physical activity and school adaptation among junior high school students. Methods: This study employed cross-sectional survey approach among junior high school students in China. Through the convenience sampling, 1,488 participants aged from 12 to 16 years old(Average age = 13.59, SD = 1.017) from two Junior high schools in Changsha City, Hunan Province were recruited to complete the Physical Activity Scale, School Adaptation Questionnaire for Junior High School Students, Resilience Scale for Adolescents, and Simple Coping Styles Questionnaire. For data analysis, the SPSS 26.0 and Amos 26.0 were used for statistical processing. Results: The results showed that physical activity exhibited a significant correlation with school adaptation (r = 0.656, p < 0.001). Resilience, positive coping style and negative coping style played partial mediating roles between physical activity and school adaptation, with the effect size were 0.229, 0.170, 0.171. The chain mediation effect size of resilience and positive coping style was 0.042, while the chain mediation effect size of resilience and negative coping style was 0.050. Conclusion: Physical activity positively predicts Chinese junior high school students’ school adaptation through resilience and coping styles, suggesting that junior high school students should engage in regular physical activity, so as to improve their resilience and positive coping styles, mitigating negative coping styles, thus promoting their school adaptation.